2014
DOI: 10.1016/j.redox.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of H2O2 in the oxidative effects of zinc exposure in human airway epithelial cells

Abstract: Human exposure to particulate matter (PM) is a global environmental health concern. Zinc (Zn2+) is a ubiquitous respiratory toxicant that has been associated with PM health effects. However, the molecular mechanism of Zn2+ toxicity is not fully understood. H2O2 and Zn2+ have been shown to mediate signaling leading to adverse cellular responses in the lung and we have previously demonstrated Zn2+ to cause cellular H2O2 production. To determine the role of Zn2+-induced H2O2 production in the human airway epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…HyPer has been chimerically linked to the growth factor receptors EGFR and PDGFR in order to create proteins positioned to sense localized increases in H 2 O 2 production [198]. Studies using HyPer have demonstrated that xenobiotic induction of H 2 O 2 is specific to subcellular compartments [114,195,199]. The group that developed HyPer recently reported an improved version, called HyPer-3, that contains point mutations that increase the sensor dynamic range [197].…”
Section: Genetically-encoded Sensors For Redox Toxicologymentioning
confidence: 99%
See 3 more Smart Citations
“…HyPer has been chimerically linked to the growth factor receptors EGFR and PDGFR in order to create proteins positioned to sense localized increases in H 2 O 2 production [198]. Studies using HyPer have demonstrated that xenobiotic induction of H 2 O 2 is specific to subcellular compartments [114,195,199]. The group that developed HyPer recently reported an improved version, called HyPer-3, that contains point mutations that increase the sensor dynamic range [197].…”
Section: Genetically-encoded Sensors For Redox Toxicologymentioning
confidence: 99%
“…This can be done using pH specific sensors such as such as pHluorin or pHluorin2 [200], albeit these sensors also emit in the green channel, requiring separate experiments or spectral unmixing [137]. pHRed is an alternative pH sensor that emits in the red channel and can therefore be co-expressed and monitored concurrently with HyPer in the same cells [199,201]. However, the ideal pH sensor to use as a control for HyPer is SypHer, which is a version of HyPer that contains a single point mutation (C199S) that renders it unable to sense H 2 O 2 [202].…”
Section: Genetically-encoded Sensors For Redox Toxicologymentioning
confidence: 99%
See 2 more Smart Citations
“…We assessed the effect of the extract on extracellular flux of mitochondrial respiration in cultured human airway epithelial cells (BEAS‐2B), as well as on expression of the heme oxygenase ( HMOX1 ) gene. We have shown previously that HMOX1 expression, a marker of oxidative stress in mammalian cells, is induced by a wide variety of air pollutants [Silbajoris et al, ; Cheng et al, ; Wages et al, ].…”
Section: Introductionmentioning
confidence: 99%